The Synthesis and Application of Novel Nanostructured Carbon Materials - Wang, Chen (Curtin University, 2018)
This study presents a comprehensive investigation on synthesis of several novel carbon materials including nitrogen-doped graphene, nitrogen-doped carbon nanotubes with encapsulated iron carbide, nitrogen-doped mesoporous carbons and Co-based nanospheres supported by carbon spheres and their applications in the catalytic oxidation of phenol solution by heterogeneous activation of peroxymonosulfate. Their structures, morphologies and relevant mechanisms were studied thoroughly. These findings would open a new avenue for the development of green catalysts in environmental remediation.